Establishing the Reliability &Validity of Scale for Smart Roads: Examining the Mediating-Moderating effects of government policies, management support, beliefs, attitude & behavior - Kundi, Ghulam Muhammad (The journal of contemporary issues in business and government, 2021)
Smart roads have transformed the conventional roads into more efficient and drivers friendly, however, the transition is not easy for both developed and developing nations. Therefore, the successful development of smart roads is possible if these countries adequately address the socio- political, psychological, organizational, cultural, financial, technological issues besides issues related to government policies, public-private partnership and support, the belief, attitude, and behavior. This study is an effort in the same line. Data was collected from Canada, France and Saudi Arabia. PLS-SEM was used for data analysis. Hierarchical multiple regression was run for moderation. The study found that innovative culture, public-private partnership, green energy, safety and security, economic sustainability, government policies, top management support, attitude and behavior are crucial for the development of smart roads. This study also suggeststhat cultural issues need to be addressed for the success of smart roads.